The Effectiveness of Science E-Magazine of Socioscientific Issues-Based Inquiry Model to Improve Critical Thinking Skill of Junior High School Students - Rika Dyanita Sari; Rudiana Agustini; Wahono Widodo (Studies in Learning and Teaching, 2021)
This study aimed to improve the students’ critical thinking ability through learning activities using a science e-magazine of socioscientific issues-based inquiry model on additive and addictive material. This study used a one-group pretest-posttest design. This study also investigated the validity, practicality, and effectiveness of the science e-magazine of socioscientific issues-based inquiry model on the students’ critical thinking abilities. Data collection techniques used validation, observation, and test. The average students’ critical thinking ability was seen from the overall n-gain score of 0.34 in moderate criteria. The data analysis technique was intended to find out the improvement of critical thinking using paired sample t-test with sig result that was 0.000, so that if H0 is rejected, it means there was an increase in the ability of critical thinking students on VIII A class at Junior High School 1 Pamekasan after the learning activities. Students’ responses and implementation were analyzed using descriptive analysis. E-magazine development was accompanied by the compiling of other learning tools such as syllabus, lesson plan, student worksheet, and critical thinking tests. E-magazine was saved in pdf format, making it easier for students to read them on smartphones or laptops. The average response of students to the learning activities was 80% and to the e-magazine was 80%.